Beyond close relationships: the positive effects of group relationships and group identification on health - Camilo, Cristina; Lima, Maria Luísa; Moura, Rita; Quintal, Fátima; Palacin-Lois, Maria (Frontiers in Social Psychology, 2024)
Introduction It is well-known that social relationships positively impact health, but the direct and indirect ways these lead to better health outcomes remain understudied. Stemming from the concept of multiple levels of analysis, we address this problem by disentangling the links between different types of social relationships and health (including physical health, mental health, and well-being), and comparing the effects of multiple mediators based on two levels of analysis: interpersonal and group. Methods We propose a model that uses loneliness and social support as proxies of personal ties (mediators between close relationships and health), and social integration and multiple identities as proxies of group ties (mediators between group relationships and health). Likewise, we also propose a moderating effect of group identification on the association between group ties and health. We collected 848 responses through a self-report online survey and used structural equation modeling (SEM) analysis to assess the proposed model. Results Data yielded that close relationships are stronger predictors of better health outcomes than group relationships. Yet, more importantly, the results also provide strong evidence for the positive effects of the group-level variables. The effect of group relationships on health is significantly positive, and this association is stronger for those who identify more with their group. Discussion Our findings are closely aligned with the notion that increasing and improving people's social network is an effective way to contribute to better social determinants of health, while demonstrating that it is important to consider which type of relationship is being fostered.